Synthesis of ternary cocrystals, salts, and hydrates of acefylline with enhanced dissolution and high permeability - Allu, Suryanarayana; Garai, Abhijit; Chernyshev, Vladimir V.; Nangia, Ashwini K. (Crystal Growth & Design, 2022)
Acefylline (ACF) is a stimulant xanthine derivative drug, which is formulated as a piperazine salt for the treatment of bronchial asthma. ACF falls under BCS class IV category of low solubility and poor permeability, which together limit the bioavailability and efficacy of the drug. In this work, ACF binary and ternary cocrystals, salts–cocrystals, and their polymorphs are synthesized by cocrystallization with several coformers. Two different methods were adopted for the supramolecular assembly of the ternary systems A.B.C: (1) first, binary adducts A.B or A.C were crystallized by grinding a slurry of the components in a suitable solvent and then C was added and grinding was continued; and (2) all three components were taken in a solvent slurry and ground together. The former method was found to be superior in affording the ternary salt/cocrystal. The role of laboratory seeding is implicated to explain the variation in crystallization results at different stages of the project. Crystal structures of the product’s binary and ternary systems were solved by single-crystal X-ray diffraction and powder X-ray diffraction data for structure solution. The crystal structures show the recurrence of carboxylate–pyridinium and imidazole–acid heterosynthons in the binary and ternary adducts. The intermolecular interactions between ACF and the coformer are analyzed by Hirshfeld surfaces, 2D fingerprint plots, and an energy framework. The permeability of ACF increases in binary and ternary systems with selected coformers. The fast dissolution and high permeability of ACF-PIP make this salt an improved crystalline formulation of acefylline.